Tingkat Pengetahuan Masyarakat Mengenai Iklan Obat Nyeri Kepala Terhadap Penggunaan Swamedikasi di Masyarakat Ance Dg Ngoyo V Kecamatan Panakukang Kota Makassar - Kadang, Yuniharce; Angriani, Riri (Jurnal Farmasi Sandi Karsa, 2023)
Medicines play an important role in health services. In terms of drug use, the most important step to consider is correct diagnosis, resulting in a rational, effective, safe and economical prescription. This research is a descriptive study aimed at finding out the level of drug use for the two biggest diseases, namely ARI and gastritis. Data collection was carried out by looking at prescriptions from people with acute respiratory infections and gastritis who entered the Tamalanrea Jaya Health Center from January to March 2023. The results of this research showed that from January to March the use of medicines decreased slightly due to the influence of good weather. From January to March, the total number of patients indicated for ISPA was 204, with the highest use of the drug dexamethasone being 1,770, while the number of patients indicated for gastritis was 180 with the highest use of the drug ranitidine being 1,460.